NF-κB SIGNALING MEDIATES THE INDUCTION OF MTA1 BY HEPATITIS B VIRUS TRANSACTIVATOR PROTEIN HBx - Bui-Nguyen, Tri M. (2009)
Metastasis-associated protein 1 (MTA1), a master chromatin modifier, has been shown to regulate cancer progression and is widely upregulated in human cancer including, hepatitis B virus-associated hepatocellular carcinomas (HCC). Here we provide evidence that hepatitis B virus transactivator protein HBx stimulates the expression of MTA1 but not MTA2 or MTA3. The underlying mechanism of HBx stimulation of MTA1 involves HBx targeting of transcription factor NF-κB and the recruitment of HBx/p65 complex to the NF-κB -consensus motif on the relaxed MTA1 gene chromatin. We also discovered that MTA1 depletion in HBx-expressing cells severely impairs the ability of HBx to stimulate NF-κB signaling and the expression of target pro-inflammatory molecules. Furthermore the presence of HBx in HBx-infected hepatocellular carcinomas correlated well with increased MTA1 and NF-κB-p65. Collectively, these findings revealed a previously unrecognized integral role of MTA1 in HBx stimulation of NF-κB signaling and consequently, the expression of NF-κB targets gene products with functions in inflammation and tumorigenesis.